Evaluating health-related quality of life in type 1 diabetes: a systematic literature review of utilities for adults with type 1 diabetes - Smith-Palmer J; Bae JP; Boye KS; Norrbacka K; Hunt B; Valentine WJ (Dove Medical Press, 2016)
Jayne Smith-Palmer,1 Jay P Bae,2 Kristina S Boye,2 Kirsi Norrbacka,3 Barnaby Hunt,1 William J Valentine1 1Ossian Health Economics and Communications GmbH, Basel, Switzerland; 2Eli Lilly and Company, Indianapolis, IN, USA; 3Eli Lilly Finland, Helsinki, Finland Background and aims: Type 1 diabetes is a chronic condition associated with micro- and macrovascular complications that have a notable impact on health-related quality of life, the magnitude of which can be quantified via the use of utility values. The aim of this review was to conduct a systematic literature review to identify and compare published health state utility values for adults with type 1 diabetes both, with and without diabetes-related complications.Methods: Literature searches of the PubMed, EMBASE, and Cochrane Library databases were performed to identify English language studies on adults with type 1 diabetes, published from 2000 onward, reporting utility values for patients with or without diabetes-related complications or assessing the impact of changes in HbA1c or body mass index on quality of life. For inclusion, studies were required to report utilities elicited using validated methods.Results: A total of 20 studies were included in the final review that included utility values elicited using the EuroQuol five dimensions questionnaire (n=9), 15D questionnaire (n=2), Quality of Well-Being scale (n=4), time trade-off (n=3), and standard gamble (n=2) methods. For patients with no complications, reported utility values ranged from 0.90 to 0.98. Complications including stroke (reported disutility range, −0.105 to −0.291), neuropathy (range, −0.055 to −0.358), and blindness (range, −0.132 to −0.208) were associated with the largest decrements in utility values. The magnitude of utility values and utility decrements was influenced by the assessment method used.Conclusion: Complications lead to impaired health-related quality of life in patients with type 1 diabetes, the magnitude of which is influenced by the method used to determine utilities. There is currently a lack of utility data for certain complications of type 1 diabetes, meaning that many economic evaluations have relied on a combination of type 1 and type 2 diabetes utilities, despite differences between the conditions and populations, or type 1 diabetes-specific utilities derived from different instruments. Keywords: type 1 diabetes, quality of life, health status, complications